Black Dialect and Learning to Read: What is the Problem? - Masland, Susan W. (Journal of Teacher Education)
The article intends to summarize evidence for and against Black dialect interference during the reading process. During the last decade, several linguists have enriched understanding of Black dialect with their detailed studies. They have provided analyses of its phonology or sound system, its vocabulary, and its syntax or grammatical structures. If dialect does interfere with reading, it would do so because of a mismatch with standard English in one or more of those three areas. A growing body of linguists and researchers claim considerable evidence for the argument that the teacher's response to dialect is a powerful determinant of whether or not a particular child will learn in that teacher's classroom. They find the teacher's response to be a negative and highly destructive one. Some historical perspective on the way Black dialect has been viewed in literature may be helpful in depicting a context within which teacher attitudes have developed. In the 1960s, there was considerable interest in determining the reasons for poor school performance of ghetto children.